Mathematics Communication Characteristics Pre-Service Teacher of Primary School in Explaining Trapesium Area Reviewed From School Origin - Abidin, Zainal ((JRAMathEdu) Journal of Research and Advances in Mathematics Education, 2018)
This study aims to know the characteristics of mathematical communication of pre-service teacher of primary school. The material used as the object of research is the material of geometry. This material in addition requires the ability of algebra and spatial skills. The trapezoidal area is chosen as the topic because among all the flat planes studied in primary school, the trapezoidal area is considered as the most complex. This is because to calculate the trapezoidal area involving 3 variables. The ability of mathematical communication involves the ability to write and the ability to explain. These abilities are reviewed from the background of students in secondary school. The subjects of this study are 15 students of PGSD STKIP Al Hikmah Surabaya in academic Year 2017 - 2018. The way of mathematical communication will be grouped according to their characteristics. The way of written communication will be sharpened by oral communication. The results will be analyzed whether there is relevance to the subject background in their secondary school (SMA, SMK, MA). The results showed that the characteristics of written communication in the form of (1) narrative, (2) procedure, (3) dialogue. While the characteristics of oral communication are shaped (1) lecture (2) Instructional (3) discussion. Pre-service teachers with high school background have better mathematical communication skills than those from SMK and MA background.Keywords: Pre-service primary school teacher, Mathematical Communication, Trapezoidal Area. Â Â